Aesthetic appreciation of Kelantan Heritage ceramics : an indicator for sustainability - Olalere, Folasayo Enoch; Ab. Aziz Shuaib (Universiti Malaysia Kelantan, 2015)
Abstract. Apart from creating clay objects with unlimited variety of shapes, the surface can also be decorated with patterns in many ways to enhance the overall appearance. As a result of this, surface decorations have been one of the major heritage values in ceramic studies. Thus, applying Gestalt theory and Golden section rule, this paper seeks to identify the unique heritage values in Kelantan traditional ceramics that can be sustained as genius loci. Pictorial data (decorative patterns) were collected by visiting six museums in Kelantan and the data were analyzed with the aid of PhiMatrix software. The result shows eleven (11) decorative patterns that conform to the golden section rule and the Gestalt principles of grouping elements. Hence, sustaining this heritage values will not only serve as identity, but also demonstrate the recognition of the beauty of the past.